Pemrosesan dan Penyimpanan Informasi pada Otak Anak dalam Belajar: Short Term and Long Term Memory - Ririn Musdalifah (IAIN PAREPARE, 2019)
Neuroscience theory is an education system that studies the nervous system. Learning theory which prioritizes processing that occurs in the brain nerves, in neuroscience itself studies neuroanatomy and neurophysiology, both of which need to be studied to improve the quality of learning that is very pleasant. Point as a goal, neuroscience learning to understand the purpose of education will increase, if you do not understand neuroscience of learning, the goals to be achieved will not rise. This paper intends to explain the processing and storing of information in short-term memory and long-term memory of early childhood brain in learning.